Subcellular architecture and metabolic connection in the planktonic photosymbiosis between Collodaria (radiolarians) and their microalgae. (1st October 2021) - Decelle, Johan; Veronesi, Giulia; LeKieffre, Charlotte; Gallet, Benoit; Chevalier, Fabien; Stryhanyuk, Hryhoriy; Marro, Sophie; Ravanel, Stéphane; Tucoulou, Rémi; Schieber, Nicole; Finazzi, Giovanni; Schwab, Yannick; et al.
Summary: Photosymbiosis is widespread and ecologically important in the oceanic plankton but remains poorly studied. Here, we used multimodal subcellular imaging to investigate the photosymbiosis between colonial Collodaria and their microalga dinoflagellate ( Brandtodinium ). We showed that this symbiosis is very dynamic whereby symbionts interact with different host cells via extracellular vesicles within the colony. 3D electron microscopy revealed that the photosynthetic apparatus of the microalgae was more voluminous in symbiosis compared to free‐living while the mitochondria volume was similar. Stable isotope probing coupled with NanoSIMS showed that carbon and nitrogen were stored in the symbiotic microalga in starch granules and purine crystals respectively. Nitrogen was also allocated to the algal nucleolus. In the host, low 13 C transfer was detected in the Golgi. Metal mapping revealed that intracellular iron concentration was similar in free‐living and symbiotic microalgae ( c . 40 ppm) and twofold higher in the host, whereas copper concentration increased in symbionts and was detected in the host cell and extracellular vesicles. Sulfur concentration was around two times higher in symbionts (chromatin and pyrenoid) than their host. This study improves our understanding on the functioning of this oceanic photosymbiosis and paves the way for more studies to further assess its biogeochemical significance.